Brief Report: Anti–RNPC‐3 Antibodies As a Marker of Cancer‐Associated Scleroderma. Issue 6 (June 2017) - Shah, Ami A.; Xu, George; Rosen, Antony; Hummers, Laura K.; Wigley, Fredrick M.; Elledge, Stephen J.; Casciola‐Rosen, Livia
Abstract : Objective: Prior studies have demonstrated an increased risk of cancer‐associated scleroderma in patients with anti–RNA polymerase III (anti–RNAP III) autoantibodies as well as in patients who are triple‐negative for anticentromere (anti‐CENP), anti–topoisomerase I (anti–topo I), and anti–RNAP III (also known as anti‐POL) autoantibodies (referred to as CTP negative). In a recent study of 16 CTP‐negative scleroderma patients with coincident cancer, 25% of the patients were found to have autoantibodies to RNPC‐3, a member of the minor spliceosome complex. This investigation was undertaken to validate the relationship between anti–RNPC‐3 antibodies and cancer and examine the associated clinical phenotype in a large sample of scleroderma patients. Methods: Scleroderma patients with cancer were assayed for anti‐CENP, anti–topo I, anti–RNAP III, and anti–RNPC‐3 autoantibodies. Disease characteristics and the cancer–scleroderma interval were compared across autoantibody groups. The relationship between autoantibody status and cancer‐associated scleroderma was assessed by logistic regression. Results: Of 318 patients with scleroderma and cancer, 70 (22.0%) were positive for anti–RNAP III, 54 (17.0%) were positive for anti–topo I, and 96 (30.2%) were positive for anti‐CENP. Twelve patients (3.8% of the overall group or 12.2% of CTP‐negative patients) were positive for anti–RNPC‐3. Patients with anti–RNPC‐3 had a short cancer–scleroderma interval (median 0.9 years). Relative to patients with anti‐CENP, patients with anti–RNPC‐3 and those with anti–RNAP III had a >4‐fold increased risk of cancer within 2 years of scleroderma onset (for anti–RNPC‐3–positive patients, odds ratio [OR] 4.3, 95% confidence interval [95% CI] 1.10–16.9 [ P  = 0.037]; for anti–RNAP III–positive patients, OR 4.49, 95% CI 1.98–10.2 [ P  < 0.001]). Patients with anti–RNPC‐3 had severe restrictive lung disease, gastrointestinal disease, Raynaud's phenomenon, and myopathy. Conclusion: Anti–RNPC‐3 autoantibodies, similar to anti–RNAP III autoantibodies, are associated with an increased risk of cancer at the onset of scleroderma. These data suggest the possibility of cancer‐induced autoimmunity in this subset of patients with scleroderma.